Systematic and Local Effect of Doxycycline and Low Intensity Laser Treatment on Periodontitis in Rats - Hassan Asghar, Amina Asghar, Chaudhry Umar Asghar, Fatima Chaudhry (Pakistan Journal of Medical & Health Sciences, 2022)
Aim: : To evaluate the systematic and local effect of doxycycline and low intensity laser treatment on periodontitis in rats. Study design: Prospective study Place and duration of study: Department of Periodontology, De’Montmorency College of Dentistry, Lahore from 1st January 2021 to 30th September 2021. Methodology: One hundred of rats (Rattus norvegicus albinus) were selected and divided into two groups. In Group I, 50 rats were given induction of periodontal disease while other 50 as Group II were not given the induction of the periodontal disease and were designated as non-treatment group. Lowe left 1st molar was covered with ten-number cotton threads using altered forceps. Group I rats were further divided into slots of ten rats depending upon the local-treatment they would be receiving including doxycycline and or low intensity laser. After seven days of receiving periodontal disease the ligature was removed from each rat. Results: The animal was euthanatized after completion of 30 days follow-up. Post-euthanasia the jaws were removed and preserved in 10% solution of formalin for a period of 48 hours. The left side was then subjected to the x ray imaging after its separation from the right side. The imaging illustrated that there was significant bone loss in the Group II. Considering the bone loss in all the groups it was observed that reduced bone loss was presented in Sub group I c, d and e than Sub group I a and Group II on day seven. Conclusion: Periodontitis was greatly reduced in doxycycline ad well as low intensity laser groups systematically as well as locally in comparison with no treatment group.